Amino-containing modified silicon dioxide, inorganic nanofiber curing agent composition and application thereof, epoxy resin composition and epoxy resin product
By using a curing agent composition containing amino-modified silica and inorganic nanofibers in epoxy resin, the problem of softening and poor compressive strength of epoxy resin proppant under high temperature and high pressure is solved, and high temperature stability and Improved compressive performance.
Patent Information
- Application Number
- CN202311773023.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-21
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-12-21
AI Technical Summary
The existing epoxy resins are softened as proppants under high temperature and high pressure conditions, have poor compressive strength, high toxicity of the curing agent and difficult to control the curing speed.
Using amino-containing modified silica and inorganic nanofiber curing agent composition, the modified nanosilicon dioxide reacts with epoxy groups in the epoxy resin and is used in combination with inorganic nanofibers to improve the curing Compressive strength and thermal stability of epoxy resin.
It is realized that the epoxy resin is not easy to soften and deform under high temperatures, while improving its compressive strength, and the curing process is controllable, avoiding the toxic effects of the curing agent.
Smart Images

Figure CN119264379A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of organic polymers, and in particular to an amino-modified silicon dioxide, an inorganic nanofiber curing agent composition and application thereof, an epoxy resin composition and an epoxy resin product. Background Art
[0002] Common types of proppants for oil fracturing mainly include natural quartz sand, artificial ceramsite, and resin-coated sand. Ideal proppants need to have high mechanical strength, high conductivity, low compatibility, low cost, low density, and are not easy to flow back and embed. However, it is often difficult to have these advantages at the same time. In order to effectively support the induced fractures under high temperature and closed pressure conditions, the proppant is required to be difficult to soften under high temperature and high pressure and have higher compressive strength.
[0003] As a traditional polymer material, epoxy resin is used in many fields, such as electronics, energy, machinery, and chemical industry. However, when used as a proppant, it must be used in conjunction with a curing agent to function. However, the epoxy curing agents on the market are not suitable for phase change fracturing fluids. The main problem is that they are mostly cured in the epoxy resin body and cannot fill cracks and microcracks of various sizes, resulting in low conductivity and difficulty in supporting the far end of the cracks. In addition, small molecule curing agents are highly toxic and cure too quickly, which is not conducive to curing speed control. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems of poor curing performance, high toxicity, difficult to control curing speed of curing agents in the prior art, poor compressive strength and easy softening of products obtained after being applied to epoxy resin, and to provide a curing agent composition containing amino-modified silica and inorganic nanofibers and its application, an epoxy resin composition and an epoxy resin product. The curing agent composition contains modified nano-silica and inorganic nanofibers with specific structures. The polyamino groups in the modified nano-silica present a dendritic morphology on the surface of the nano-silica. When the modified nano-silica is added to the epoxy resin, it can undergo a bonding reaction with the epoxy groups in the epoxy resin, giving full play to the advantages of the two. At the same time, when used in combination with the inorganic nanofibers, the cured epoxy resin has greater compressive strength and is not easy to soften.
[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a curing agent composition, wherein the curing agent composition comprises a curing agent, inorganic nanofibers and water;
[0006] The curing agent is modified nano-silicon dioxide shown in formula I;
[0007]
[0008] In Formula I, M is a nano-silicon dioxide particle, x is an integer of 1-4, and R is an alkyl group with 1-4 carbon atoms;
[0009] n is an integer from 0 to 3, m is an integer from 1 to 3, n+m=3;
[0010] A is a structural unit derived from an acid anhydride compound, and B is a structural unit derived from a polyamino compound.
[0011] The second aspect of the present invention provides use of the curing agent composition described in the first aspect of the present invention as a curing agent in epoxy resin.
[0012] A third aspect of the present invention provides an epoxy resin composition, wherein the epoxy resin composition comprises an epoxy resin and a curing agent;
[0013] The curing agent is the curing agent composition described in the first aspect of the present invention;
[0014] Wherein, the epoxy resin and the curing agent exist independently.
[0015] A fourth aspect of the present invention provides an epoxy resin product, which is obtained by mixing and curing the epoxy resin composition described in the third aspect of the present invention.
[0016] Through the above technical scheme, the amino-modified silica, inorganic nanofiber curing agent composition and application, epoxy resin composition and epoxy resin product provided by the present invention obtain the following beneficial effects: the polyamino groups in the modified nanosilica present a dendritic morphology on the surface of the nanosilica, and when the modified nanosilica is added to the epoxy resin, it can undergo a bonding reaction with the epoxy groups in the epoxy resin, giving full play to the advantages of the two, and at the same time, when used in combination with the inorganic nanofiber, the cured epoxy resin can be used as a proppant, which can have a large compressive strength while not being easy to soften, and is not easy to deform at high temperatures. DETAILED DESCRIPTION
[0017] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0018] A first aspect of the present invention provides a curing agent composition, wherein the curing agent composition comprises a curing agent, inorganic nanofibers and water;
[0019] The curing agent is modified nano-silicon dioxide shown in formula I;
[0020]
[0021] In Formula I, M is a nano-silicon dioxide particle, x is an integer of 1-4, and R is an alkyl group with 1-4 carbon atoms;
[0022] n is an integer from 0 to 3, m is an integer from 1 to 3, n+m=3;
[0023] A is a structural unit derived from an acid anhydride compound, and B is a structural unit derived from a polyamino compound.
[0024] In the present invention, the surface of the nano-silica particle M is modified with multiple amino groups, and the amino groups on the surface of the nano-silica particle M present a dendritic morphology. When the modified nano-silica is added to the epoxy resin, it can undergo a bonding reaction with the epoxy groups in the epoxy resin, giving full play to the advantages of both. At the same time, when used in combination with the inorganic nanofiber, the cured epoxy resin can be used as a proppant, which can have a large compressive strength while not being easy to soften and not being easy to deform at high temperatures.
[0025] According to the present invention, in Formula I, the acid anhydride compound is selected from at least one of maleic anhydride, phthalic anhydride and succinic anhydride.
[0026] According to the present invention, the polyamino compound has a linear polyethylene polyamino compound or a nonlinear polyethyleneimine having a number average molecular weight of 300-3000, which is a structure shown in Formula II:
[0027]
[0028] Here, p is an integer from 1 to 6.
[0029] In the present invention, the polyamino compound is selected from the above compounds, so that the amino content in the modified nano-silicon dioxide is high, and the curing performance of epoxy resin is further improved.
[0030] According to the present invention, the particle size of the nano-silicon dioxide particles M is 10-500nm, and the specific surface area is 10-300m 2 / g.
[0031] According to the present invention, the particle size of the modified nano-silicon dioxide is 10-500nm, and the specific surface area is 50-500m 2 / g.
[0032] According to the present invention, the particle size dispersion coefficient of the modified nano-silicon dioxide is 0.09-0.15.
[0033] According to the present invention, the amino content of the modified nano-silicon dioxide is 0.1-5 mmol / g.
[0034] In the present invention, the modified nano-silicon dioxide can be prepared according to the following steps:
[0035] S1. In the presence of a protective gas, dispersing nano-silica particles M in a first solvent, adding aminosilane to carry out a first reaction, and obtaining amino-functionalized nano-silica as shown in formula III;
[0036]
[0037] S2, in the presence of a second solvent, subjecting the amino-functionalized nano-silica to a second reaction with an acid anhydride compound to obtain a carboxyl-functionalized nano-silica of formula IV;
[0038]
[0039] S3. In the presence of an alkaline catalyst, the carboxyl-functionalized nano-silica is mixed with a condensation agent, activated, and then a polyamino compound is added to carry out a third reaction to obtain modified nano-silica.
[0040] In the present invention, the protective gas is nitrogen and / or an inert gas.
[0041] In the present invention, steps S1, S2 and S3 each independently comprise separation, washing and drying steps.
[0042] Furthermore, there is no particular limitation on the separation method, and for example, it may be at least one of filtration, rotary evaporation or centrifugal separation.
[0043] Furthermore, there is no particular limitation on the washing conditions. For example, the washing can be performed 3-4 times using conventional solvents in the art, wherein the solvent can be at least one of methanol, ethanol, and acetone. Preferably, in step S1, acetone and dichloromethane are used for washing.
[0044] According to the present invention, in step S1, the mass ratio of the nano-silica particles M to the aminosilane is 5-100:1.
[0045] Furthermore, the mass ratio of the nano-silica particles M to the aminosilane is 10-50:1.
[0046] According to the present invention, the aminosilane is at least one selected from aminopropyltriethoxysilane, aminopropyltrimethoxysilane, aminopropylmethyldimethoxysilane and aminopropylmethyldiethoxysilane.
[0047] According to the present invention, the conditions of the first reaction include: reaction temperature of 120-160° C., and reaction time of 2-24 h.
[0048] According to the present invention, in step S2, the mass ratio of the amino-functionalized nano-silica to the acid anhydride compound is 5-100:1.
[0049] According to the present invention, the acid anhydride compound is at least one selected from maleic anhydride, phthalic anhydride and succinic anhydride.
[0050] According to the present invention, the conditions of the second reaction include: reaction temperature of 90-160° C., and reaction time of 2-12 h.
[0051] According to the present invention, the first solvent and the second solvent are each independently selected from at least one of toluene, xylene, benzene and N,N-dimethylformamide.
[0052] According to the present invention, in step S3, the mass ratio of the carboxyl-functionalized nano-silica, the condensation agent, the alkaline catalyst and the polyamino compound is 1:0.05-0.5:0.01-0.1:0.1-5.
[0053] In the present invention, when the mass ratio of the carboxyl-functionalized nano-silica, the condensing agent, the alkaline catalyst and the polyamino compound meets the above preferred range, the obtained modified nano-silica has the best comprehensive performance and further improves the curing performance of epoxy resin.
[0054] According to the present invention, the condensing agent is selected from one of dicyclohexylcarbodiimide, diisopropylcarbodiimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide.
[0055] According to the present invention, the base catalyst is selected from at least one of 4-dimethylaminopyridine, 1,8-diazabicycloundec-7-ene and triethylamine.
[0056] According to the present invention, the conditions of the third reaction include: reaction temperature of 0-40°C, reaction time of 2-48h.
[0057] According to the present invention, in step S3, the activation conditions include: activation temperature of 10-25° C., and activation time of 8-24 h.
[0058] According to the present invention, the diameter of the inorganic nanofiber is 500-900 nm, and the aspect ratio is 10-20:1.
[0059] In the present invention, the diameter and aspect ratio of the inorganic nanofibers meet the above ranges, and can be used as an epoxy resin curing agent reinforcing agent to have the characteristics of significant reinforcement without clogging pores.
[0060] Furthermore, the inorganic fiber has a diameter of 500-600 nm and an aspect ratio of 16-20:1.
[0061] According to the present invention, the inorganic nanofiber is selected from at least one of carbon fiber, SiC fiber, ceramic fiber and nano glass fiber.
[0062] Furthermore, the inorganic nanofibers are nanoglass fibers.
[0063] According to the present invention, based on the total weight of the curing agent composition, the content of the curing agent is 40-70 parts by weight, the content of the inorganic nanofibers is 0.2-1 parts by weight, and the content of water is 29-50 parts by weight.
[0064] In the present invention, the components in the curing agent composition meet the above ranges, and the components synergize with each other, so that when the composition is applied to epoxy resin, the compressive strength of the epoxy resin after curing is further improved, and the cured epoxy resin is not easily deformed at high temperatures.
[0065] Furthermore, based on the total weight of the curing agent composition, the content of the curing agent is 45-60 parts by weight, the content of the inorganic nanofibers is 0.3-0.8 parts by weight, and the content of water is 35-50 parts by weight.
[0066] According to the present invention, the curing agent composition further comprises 2-5 parts by weight, preferably 2.5-4 parts by weight of an accelerator.
[0067] According to the present invention, the accelerator is selected from polycarboxylic acids and / or small molecule polyamines.
[0068] According to the present invention, the polycarboxylic acid is at least one selected from terephthalic acid (PTA), citric acid (CA), tartaric acid, oxalic acid, malic acid, citric acid and ascorbic acid.
[0069] According to the present invention, the small molecule polyamine is at least one selected from polyethylene polyamine, ethylenediamine, 1,6-hexanediamine, isophoronediamine, 2-methyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, hydrazine and dihydrazide.
[0070] According to the present invention, the accelerator is a mixture of polycarboxylic acid and small molecule polyamine, wherein the mass ratio of the polycarboxylic acid to the small molecule polyamine is 1:0.1-0.8.
[0071] In the present invention, the accelerator is a mixture of polycarboxylic acid and small molecule polyamine, which can improve the high temperature resistance of the curing agent composition while ensuring its fluidity. Further, when the mass ratio of the polycarboxylic acid to the small molecule polyamine meets the above range, the high temperature resistance of the curing composition can be significantly improved.
[0072] Furthermore, the mass ratio of the polycarboxylic acid to the small molecule polyamine is 1:0.4-0.7.
[0073] According to the present invention, at 25° C., the apparent viscosity of the curing agent composition is 100-400 mPa·s, preferably 150-250 mPa·s.
[0074] The second aspect of the present invention provides a use of the curing agent composition described in the first aspect of the present invention as a curing agent in epoxy resin.
[0075] A third aspect of the present invention provides an epoxy resin composition, wherein the epoxy resin composition comprises an epoxy resin and a curing agent;
[0076] The curing agent is the curing agent composition described in the first aspect of the present invention;
[0077] Wherein, the epoxy resin and the curing agent exist independently.
[0078] In the present invention, the epoxy resin and the curing agent in the epoxy resin composition are stored separately and independently, which can prevent the epoxy resin from curing in advance and affecting the subsequent normal use. When used in the subsequent process, the epoxy resin and the curing agent are injected into the formation at the same time to perform a curing reaction under the formation, so that the honeycomb product is used as a proppant.
[0079] According to the present invention, the amount of the curing agent is 40-80 parts by weight relative to 100 parts by weight of the epoxy resin.
[0080] In the present invention, the amount of the curing agent used satisfies the above range, so that the cured epoxy resin product has a higher compressive strength and is not easily deformed at high temperatures.
[0081] Furthermore, relative to 100 parts by weight of the epoxy resin, the amount of the curing agent is 60-70 parts by weight.
[0082] A fourth aspect of the present invention provides an epoxy resin product, which is obtained by mixing and curing the epoxy resin composition described in the third aspect of the present invention.
[0083] According to the present invention, at 120° C. and 50 MPa, the deformation rate of the epoxy resin product is less than or equal to 4%, preferably less than or equal to 1%.
[0084] According to the present invention, the softening point of the epoxy resin product is 110-140°C, preferably 130-140°C.
[0085] In the present invention, the epoxy resin product can achieve long-term pressure-bearing operation at 120° C.-130° C.
[0086] The present invention will be described in detail below by way of examples. In the following examples,
[0087] The particle size of modified nano-silica was measured by transmission electron microscopy (TEM) and scanning electron microscopy (SEM);
[0088] The specific surface area of modified nano-silica was measured by BET adsorption method;
[0089] The particle size dispersion index (PDI) of modified nano-silica was measured by laser particle size analyzer (DLS);
[0090] The amino content in modified nano-silica was measured by acid-base neutralization titration method;
[0091] The diameter of inorganic nanofibers was measured by scanning electron microscopy (SEM) method;
[0092] The aspect ratio of inorganic nanofibers was measured by scanning electron microscopy (SEM);
[0093] The apparent viscosity of the curing agent composition was measured by a six-speed rotational viscometer method;
[0094] The glass transition temperature of epoxy resin products is measured by DSC method;
[0095] The deformation rate of epoxy resin products is measured according to the following method:
[0096] At normal pressure and 25°C, the diameter of the epoxy resin product tested is D0. At 50MPa and 120°C, the epoxy resin product is extruded using a high and low temperature universal material testing machine. The diameter of the epoxy resin product after extrusion is D1. The deformation rate = (D0-D1) / D0×100%.
[0097] The permeability change rate of epoxy resin products is measured according to the following method:
[0098] At room temperature and 40 MPa, the permeability of the initial epoxy resin product is tested as M0. After the initial epoxy resin product is placed at 120°C and 40 MPa for 30 days, its permeability M1 is tested again. The permeability change rate = (M0-M1) / M0×100%. Among them, the permeability of the epoxy resin product is tested using a high-pressure displacement device and is tested in accordance with the enterprise standard Q / SH1020 "Method for Determining the Permeability of High Permeability Consolidated Cores" of Sinopec Shengli Oilfield Administration.
[0099] The raw materials used in the following examples and comparative examples are all commercially available products, and the parameters of the inorganic nanofibers are as follows:
[0100] S1: diameter 500nm, aspect ratio 20:1;
[0101] S2: diameter 550nm, aspect ratio 10:1;
[0102] S3: diameter 400nm, aspect ratio 8:1.
[0103] The modified nano silicon dioxide M1-M2 is prepared according to the following method:
[0104] Preparation of Nano-Silica M1
[0105] S1. Preparation of aminopropyl functionalized nano-silica:
[0106] Weigh 2g of the average particle size of 30nm and the specific surface area of 200m 2 / g of nano-silica particles were dispersed in 100mL of anhydrous toluene, and then 0.2g of aminopropyltriethoxysilane was added. The mixture was refluxed and stirred at 150°C for 24 hours under nitrogen protection. After the reaction, the solid product was centrifuged to obtain the solid product. The solid product was repeatedly washed with acetone and dichloromethane for 3 times, and vacuum dried at 40°C for 12 hours to obtain aminopropyl-functionalized nano-silica.
[0107] S2. Preparation of carboxyl functionalized nano-silica:
[0108] Weigh 2 g of the aminopropyl-functionalized nano-silica prepared above, disperse it in 50 mL of xylene, add 0.2 g of maleic anhydride, reflux and stir at 160 ° C for 6 hours under nitrogen protection, wash it repeatedly with methanol 3 times after the reaction, and vacuum dry it at 40 ° C for 12 hours to obtain carboxyl-functionalized nano-silica.
[0109] S3. Preparation of modified nano-silica:
[0110] Weigh 1 g of the carboxyl-functionalized nano-silica prepared above, disperse it in 50 mL of toluene, add 0.25 g of diisopropylcarbodiimide (DIC) and 0.06 g of 1,8-diazabicycloundec-7-ene (DBU), stir and activate at room temperature (25°C) for 1 hour, then add 4 g of polyethyleneimine (number average molecular weight of 1500), continue to react at room temperature for 12 hours, wash it repeatedly with methanol 3 times after the reaction, and vacuum dry it at 40°C for 12 hours to obtain modified nano-silica M1 with formula I structure, wherein n is 0, m is 3, and x is 3.
[0111] The particle size of the modified nano-silicon dioxide M1 is 30 nm and the specific surface area is 300 m 2 / g, the amino content is 2mmol / g, and the dispersion coefficient PDI is 0.11.
[0112] Preparation of Nano-Silica M2
[0113] The preparation method of M1 was followed, except that the specific surface area of the nano-silica particles was 100 m 2 / g, and in step S3, the amount of polyethyleneimine used is 0.4g; the particle size of the modified nano-silicon dioxide M2 is 30nm, and the specific surface area is 230m 2 / g, the amino content is 0.1mmol / g, and the dispersion coefficient PDI is 0.13.
[0114] The following preparation examples and comparative preparation examples are used to illustrate the preparation of the curable resin composition.
[0115] Preparation Example 1
[0116] 48 g of modified nano-silica, 0.72 g of polyethylene polyamine, 1.8 g of terephthalic acid, 0.3 g of inorganic nanofibers, and 49.68 g of water were mixed and stirred uniformly to obtain a curing agent composition A1. The apparent viscosity of the curing agent composition A1 was tested to be 225 mPa·s.
[0117] Preparation Examples A2-A10
[0118] The curing agent composition A was prepared according to the method of Preparation Example 1, except that the types and amounts of the curing agent, accelerator, and nanofibers were different from those in Preparation Example 1, as shown in Table 1. The apparent viscosities of the curing agent compositions A2-A10 are shown in Table 3.
[0119] Table 1
[0120]
[0121] Comparative Preparation Examples 1-3
[0122] Curing agent compositions D1-D3 were prepared according to the method of Preparation Example 1, except that the types and amounts of curing agent, accelerator and nanofiber were different from those in Preparation Example 1, as shown in Table 2. The apparent viscosities of curing agent compositions D1-D3 are shown in Table 3.
[0123] Table 2
[0124]
[0125] * Water-dispersed SiO2
[0126] Table 3
[0127] Curing agent composition Apparent viscosity / mPa·s A1 225 A2 192 A3 189 A4 267 A5 243 A6 156 A7 174 A8 186 A9 309 A10 396 D1 627 D2 750 D3 96
[0128] The following examples are used to illustrate the preparation of epoxy resin products.
[0129] Examples 1-10
[0130] The curing agent composition prepared in Preparation Examples 1-10 was mixed with epoxy resin E51 and cured at a curing temperature of 120°C for 4 hours to obtain epoxy resin products P1-P10. The specific types and amounts of the raw materials are shown in Table 4, and the deformation rate, softening point and permeability change rate thereof were tested at 120°C and 50MPa, and the results are shown in Table 4.
[0131] Example 11 and Example 12
[0132] The method of Example 1 is followed, except that the amounts of the curing agent composition and the epoxy resin E51 are different, as shown in Table 4. The deformation rate, softening point and permeability change rate are tested at 120° C. and 50 MPa, and the results are shown in Table 4.
[0133] Comparative Examples 1-3
[0134] The curing agent composition prepared in Comparative Preparation Examples 1-3 was mixed with epoxy resin E51 and cured at a curing temperature of 120°C for 4 hours to obtain epoxy resin products DP1-DP3, the types and amounts of which are detailed in Table 4. The deformation rate, softening point and permeability change rate were tested at 120°C and 50 MPa, and the results are shown in Table 4.
[0135] Comparative Example 4
[0136] The epoxy resin product DP4 was prepared according to the method of Example 1, except that the amounts of the curing agent composition and the epoxy resin E51 were different, as shown in Table 4. The deformation rate, softening point and permeability change rate were tested at 120°C and 50 MPa, and the results are shown in Table 4.
[0137] Table 4
[0138]
[0139]
[0140] According to the above results, it can be seen that Examples 1-12 of the present invention achieve good technical effects, the deformation rate of the cured epoxy resin at 120° C. and 50 MPa is not greater than 2%, and the softening point is not less than 110° C. And the permeability change rate after 30 days is not greater than 3%.
[0141] Furthermore, preferred embodiments 1-2 and 5 achieve significantly better technical effects. Specifically, the deformation rate of the cured epoxy resin at 120° C. and 50 MPa is not greater than 0.7%, and the softening point is not less than 125° C., and the permeability change rate after 30 days is not greater than 1.5%.
[0142] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A curing agent composition, characterized in that The curing agent composition comprises a curing agent, inorganic nanofibers and water; The curing agent is modified nano-silicon dioxide shown in formula I; In Formula I, M is a nano-silicon dioxide particle, x is an integer of 1-4, and R is an alkyl group with 1-4 carbon atoms; n is an integer from 0 to 3, m is an integer from 1 to 3, n+m=3; A is a structural unit derived from an acid anhydride compound, and B is a structural unit derived from a polyamino compound.
2. The curing agent composition according to claim 1, wherein In Formula I, the acid anhydride compound is selected from at least one of maleic anhydride, phthalic anhydride and succinic anhydride; Preferably, the polyamino compound has a linear polyethylene polyamino compound or a nonlinear polyethyleneimine having a number average molecular weight of 300-3000 having a structure shown in Formula II: Here, p is an integer from 1 to 6.
3. The curing agent composition according to claim 1 or 2, wherein The particle size of the nano-silicon dioxide particles M is 10-500nm, and the specific surface area is 10-300m 2 / g; Preferably, the particle size of the modified nano-silicon dioxide is 10-500nm and the specific surface area is 50-500m 2 / g; Preferably, the particle size dispersion coefficient of the modified nano-silicon dioxide is 0.09-0.15; Preferably, the amino content of the modified nano-silica is 0.1-5 mmol / g.
4. The curing agent composition according to any one of claims 1 to 3, wherein The inorganic nanofibers have a diameter of 500-900 nm and an aspect ratio of 10-20:1; Preferably, the inorganic fiber has a diameter of 500-600 nm and an aspect ratio of 16-20:
1.
5. The curing agent composition according to any one of claims 1 to 4, wherein The inorganic nanofiber is selected from at least one of carbon fiber, SiC fiber, ceramic fiber and nano glass fiber, preferably nano glass fiber.
6. The curing agent composition according to any one of claims 1 to 5, wherein Based on the total weight of the curing agent composition, the content of the curing agent is 40-70 parts by weight, the content of the inorganic nanofiber is 0.2-1 parts by weight, and the content of the water is 29-50 parts by weight; Preferably, based on the total weight of the curing agent composition, the content of the curing agent is 45-60 parts by weight, the content of the inorganic nanofibers is 0.3-0.8 parts by weight, and the content of water is 35-50 parts by weight.
7. The curing agent composition according to any one of claims 1 to 6, wherein The curing agent composition further comprises 2-5 parts by weight, preferably 2.5-4 parts by weight of an accelerator; Preferably, the accelerator is selected from polycarboxylic acids and / or small molecule polyamines; Preferably, the polycarboxylic acid is selected from at least one of terephthalic acid, citric acid, tartaric acid, oxalic acid, malic acid, citric acid and ascorbic acid; Preferably, the small molecule polyamine is selected from at least one of polyethylene polyamine, ethylenediamine, 1,6-hexanediamine, isophoronediamine, 2-methyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, hydrazine and bishydrazide.
8. The curing agent composition according to claim 7, wherein The accelerator is a mixture of polycarboxylic acid and small molecule polyamine, wherein the mass ratio of the polycarboxylic acid to the small molecule polyamine is 1:0.1-0.8, preferably 1:0.4-0.
7.
9. The curing agent composition according to any one of claims 1 to 8, wherein At 25° C., the apparent viscosity of the curing agent composition is 100-400 mPa·s, preferably 150-250 mPa·s.
10. Use of the curing agent composition according to any one of claims 1 to 9 as a curing agent in epoxy resin.
11. An epoxy resin composition, characterized in that The epoxy resin composition comprises an epoxy resin and a curing agent; The curing agent is the curing agent composition according to any one of claims 1 to 9; Wherein, the epoxy resin and the curing agent exist independently.
12. The epoxy resin composition according to claim 11, wherein Relative to 100 parts by weight of the epoxy resin, the amount of the curing agent is 40-80 parts by weight, preferably 60-70 parts by weight.
13. An epoxy resin product, characterized in that: The epoxy resin product is obtained by mixing and curing the epoxy resin composition according to claim 11 or 12.
14. The epoxy resin product according to claim 13, wherein: At 120°C and 50MPa, the deformation rate of the epoxy resin product is less than or equal to 4%, preferably less than or equal to 1%; Preferably, the softening point of the epoxy resin product is 110-140°C, preferably 130-140°C.
Citation Information
Patent Citations
Epoxy glass fiber and high-silica sand core packing material and preparation method thereof
CN102634168A
Preparation of epoxy-terminated hyperbranched polyester modified nano silica organic-inorganic hybrid material
CN106565963A
Fiber-reinforced foamed epoxy resin composite material
CN108659459A
Light high-strength automobile side door plate and preparation method thereof
CN108690326A
Epoxy resin composition, preparation method and application thereof, LED display screen, packaging method of LED display screen and electronic product
CN116063818A